The Utilization of QGIS in Determining the Route and Location of the Optimal Feeder Wirawiri FD09 Bus Stop in the Unesa Ketintang Campus Area: Pemanfaatan QGIS dalam Penentuan Rute dan Lokasi Halte Optimal Feeder Wirawiri FD09 di Kawasan Kampus Unesa Ketintang - Irfan Zhain; Prathita Muti'a Yuzaeva (Universitas Negeri Surabaya, 2026)
Student commuting to the Unesa Ketintang Campus often causes traffic congestion due to the dominance of private vehicles and underutilized public transportation. This study aims to determine the optimal route for the Wirawiri FD09 feeder bus and strategic stop locations through Origin-Destination Matrix and GIS-based Multi Criteria Analysis. A quantitative descriptive-analytical approach with spatial analysis using QGIS was employed to analyze travel patterns, demand potential, and service accessibility. The results indicate that 67% of respondents (254 students) are willing to shift to the feeder service if the route enters the campus and stops are located near faculties. Based on spatial analysis with a 300–400meter walking radius, this study recommends adjusting alternative routes into the campus and establishing four new stops: the Informatics Engineering, Tennis Court, Faculty of Economics and Business, and Front Gate stops. The application of QGIS effectively provides measurable, data-driven spatial recommendations. These route and stop adjustments are expected to enhance academic mobility efficiency and support sustainable urban transportation systems.